2021
DOI: 10.3390/pharmaceutics13020241
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Binders in Twin-Screw Wet Granulation

Abstract: The binders povidone (Kollidon 30), copovidone (Kollidon VA64), hypromellose (Pharmacoat 606), and three types of hyprolose (HPC SSL‑SFP, HPC SSL, and HPC SL‑FP) were evaluated regarding their suitability in twin-screw wet granulation. Six mixtures of lactose and binder as well as lactose without binder were twin-screw granulated with demineralized water at different barrel fill levels and subsequently tableted. A screening run with HPC SSL determined the amount of water as an influential parameter for oversiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 39 publications
(65 reference statements)
0
7
0
Order By: Relevance
“…Comparing the PCT-hpc15/PRP and PRP-hpmc10/PCT tablets, the former showed greater toughness (1.53 compared to 0.66 mJ) and tensile strength (2.93 MPa compared to 2.23 MPa). The greater toughness and strength of PCT-hpc15/PRP are partly due to the higher polymer content (15% vs. 10%) and partly due to the higher strength of HPC bonds [ 36 ]. The slopes of the curves of the green tablets in the initial linear elastic region (up to 0.4 mm displacement) appear similar for the three drug mixture tablets with physical mixture having lower elastic modulus (258.6 MPa) followed by PCThpc15/PRP (268.3 MPa) and PRP-hpmc10/PCT (295 MPa).…”
Section: Resultsmentioning
confidence: 99%
“…Comparing the PCT-hpc15/PRP and PRP-hpmc10/PCT tablets, the former showed greater toughness (1.53 compared to 0.66 mJ) and tensile strength (2.93 MPa compared to 2.23 MPa). The greater toughness and strength of PCT-hpc15/PRP are partly due to the higher polymer content (15% vs. 10%) and partly due to the higher strength of HPC bonds [ 36 ]. The slopes of the curves of the green tablets in the initial linear elastic region (up to 0.4 mm displacement) appear similar for the three drug mixture tablets with physical mixture having lower elastic modulus (258.6 MPa) followed by PCThpc15/PRP (268.3 MPa) and PRP-hpmc10/PCT (295 MPa).…”
Section: Resultsmentioning
confidence: 99%
“…However, this could not be generalized, as it was observed that by inclusion of, for example, hydroxypropyl methylcellulose (HPMC) E15 in the formulation, higher friabilities were observed compared to pure mannitol granules. Similarly, Köster et al [5] demonstrated that inclusion of HPMC Pharmacoat 606 resulted in more fines in the lactose-based formulation compared to pure lactose granules. Furthermore, both studies highlighted a negative impact of binders on disintegration times, with some binders resulting in unacceptably long disintegration times [4,5].…”
mentioning
confidence: 95%
“…Similarly, Köster et al [5] demonstrated that inclusion of HPMC Pharmacoat 606 resulted in more fines in the lactose-based formulation compared to pure lactose granules. Furthermore, both studies highlighted a negative impact of binders on disintegration times, with some binders resulting in unacceptably long disintegration times [4,5]. Nevertheless, disintegrants were hypothesized to be able to compensate for the delay in disintegration due to the inclusion of a binder.…”
mentioning
confidence: 95%
See 2 more Smart Citations